Perception of time compressed speech in bilinguals - N, Sheets Vasudevan (Journal of All India Institute of Speech and Hearing)
The present investigation reports on the performance of thirty young adults (native and non-native speakers of Hindi with a high level of proficiency in English) on the time compressed version of English and Hindi sentences. The study aimed at - Analysing the influence of time compression (40, 50, and 60 percent compressin rates) on sentential stimuli in English and Hindi. - Establishing, if any, the differences between the perception of time compressed speech stimuli in English and Hindi by Speakers proficient in both the languages. - Evaluating the effects of levels of proficiency in a language on the perception of time compressed stimuli.